HUBUNGAN CARA BELAJAR SISWA DENGAN HASIL BELAJAR MATA DIKLAT STATIKA SISWA KELAS X KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN DI SMKN 5 PADANG - 374-380 , Ahmad Taher Hasibuan (CIVED, 2014)
ABSTRACT   This research is purposed to find out the relationship of students’ learning style and students’ grade for statics subject matter at X class building engineering drawing competence skill, SMKN 5 Padang. The type of this research is descriptive correlation. Subject of this research is students of X 1 and 2 classes building engineering drawing who learn statics subject matter in year of school 2013/2014. Data collection is made by questionnaire and documentation. Results of this research show that achievement degree of students’ learning style, amount to 48 students, of X class competence skill are 73.49%, that is fairly with correlation value is 0.026 which is very low correlation. Based on this research, it can be concluded that students’ grade is not dominant related to students’ learning style. Keywords: learning style, learning grade